Institucionalização de estruturas e processos de Ti : uma análise das pressões isomórficas que influenciam o processo de institucionalização da Ti de um órgão do judiciário brasileiro - Louro, Almir Costa (2014)
Orlikowski and Barley (2001) show the importance to research IT from the perspective of organizational studies, especially when is used neoinstitucional analysis, because there is more systemic understanding of how technology is intertwined in complex int